Clinical duration of action of different botulinum toxin types in humans. (May 2020) - Eleopra, Roberto; Rinaldo, Sara; Montecucco, Cesare; Rossetto, Ornella; Devigili, Grazia
Abstract: The Botulinum NeuroToxin (BoNT) comprises several serotypes with distinct properties, mechanisms of action, sensitivity and duration of effect in different species. The serotype A (BoNT/A) is the prevalent neurotoxin applied in human's disease. In this paper we present an overview of the current knowledge regarding the duration of effect and the neuromuscular sprouting of different BoNT serotypes in humans. Then, we report the original results of a study in healthy subjects treated with BoNT/A, B, C and F using different neurophysiological techniques. Twelve healthy volunteers (7 men, 5 women) are treated with BoNT/A, B, C and F or placebo in Abductor digiti minimi (ADM) muscle of the hand. Before and after injections, an extensive neurophysiological study is performed with the CMAP amplitude variation, Multi-Motor Unit Action Potentials (MUAPs) analysis, the Turns/Amplitude ratio of interference pattern (IP) and determination of jitter and Fiber Density (FD) at single-fiber electromyography (SFEMG), at week 2 (w2), 4 (w4), 6 (w6) and 8 (w8). A maximal neuromuscular block is obtained at w2 for all the serotypes. Afterwards, the CMAP trend appear similar for BoNT/A, B, and C while, BoNT/F shows a faster recover. Multi-MUAPs analysis and IP detect mild changes at w2 for all serotypes, except for BoNT/F that shows a greater change since w4. SFEMG have minimal changes in FD while, Jitter increase at w2 with a slower decrease over the time for all BoNTs. In conclusion, BoNT/F has earlier sprouting and complete recovery at w8. Other serotypes present a slower and similar profile. The EMG appear useful to study the functional recovery in humans, and these results should provide new evidence for assessing different serotypes. These findings improve our knowledge regarding the methods to evaluate duration of effects and dose equivalents in different serotypes, that in the future could change the clinicians strategy for disease-tailored BoNT therapies. Graphical abstract: Image 1 Highlights: Each BoNT serotype has distinct action in humans. Duration of effect was measures by neurophysiological testing or clinical scales. A review of clinical duration is reported.